2023
DOI: 10.1039/d2an01946a
|View full text |Cite
|
Sign up to set email alerts
|

A clinical Raman spectroscopy imaging system and safety requirements for in situ intraoperative tissue characterization

Abstract: Raman spectroscopy imaging is a technique that can be adapted for intraoperative tissue characterization to be used for surgical guidance. Here we present a macroscopic line scanning Raman imaging system...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Nonetheless, comparable studies have demonstrated effective results through algorithmic processing ( 62 ). A secondary limitation lies in the non-application of the model machine in vivo due to potential challenges the probe might introduce to surgical sterility requirements ( 63 ). Furthermore, the portable fiber-optic Raman spectrometer has yet to be fully integrated, thus impeding true portability.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, comparable studies have demonstrated effective results through algorithmic processing ( 62 ). A secondary limitation lies in the non-application of the model machine in vivo due to potential challenges the probe might introduce to surgical sterility requirements ( 63 ). Furthermore, the portable fiber-optic Raman spectrometer has yet to be fully integrated, thus impeding true portability.…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved multiple ways, including, for example, using a spectrophotometer with increased light sensitivity (e.g., HT rather than EH spectrometer from EmVision LLC) and a more powerful laser, within the maximum permissible exposure limits to ensure minimal tissue damage from increased temperature (e.g., <43°C). 50 Other more stringent safety standards as set by ANSI Z136.3 Laser Safety in Healthcare for skin and ocular exposition could be addressed through user guidelines and using safety goggles.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The scientific community has recognized that Raman spectroscopy faces several problems, including weak signals, long acquisition times, fluorescence interference in biological samples, time-consuming data processing, and high cost. [236] However, significant advances have been made over the past few decades with continuous advances in instrumentation technology and machine learning to address these challenges. To overcome the signal weakness and improve the SNR, complementary techniques such as SERS, RRS, and SRS have been widely used, which provide strong support for Raman spectroscopy.…”
Section: Discussionmentioning
confidence: 99%